TOXIC AND HAZARDOUS WASTE (B3) MANAGEMENT AT PT. PAL INDONESIA (PERSERO) - Nur Lina (Universitas Airlangga, 2021)
ABSTRACTPT. PAL Indonesia (Persero) is a state-owned enterprise (BUMN) engaged in the shipbuilding industry. Disposal of hazardous and toxic waste (B3) produced by PT. PAL Indonesia can cause negative impacts on the environment and health if special handling procedures are not taken. In order to avoid this, PT. PAL Indonesia (Persero) carries out B3 waste management. The purpose of this study was to provide an overview of the implementation of B3 waste management in PT. PAL Indonesia (Persero), including identification of B3 waste, packaging and labeling B3 waste, storage, collection and transportation of B3 waste. The research method used was the qualitative descriptive method with data collection techniques of observation, interviews, and documentation. The instrument in this study was a questionnaire. The results of the study show that in the production process, PT. PAL Indonesia (Persero) produced hazardous and toxic (B3) waste in the form of solid and liquid B3 waste in the form of used TL lamps, contaminated cotton waste, silica sand from sand blasting processes, used oil, and sludge oil. The B3 waste contained heavy metals such as Pb, Cu, Hg, Fe, and Zn. The conclusion of this research is that the implementation of B3 waste management in PT. PAL Indonesia (Persero) has not complied with implemented regulations. This study suggests the supervision of B3 waste management in PT. PAL Indonesia (Persero) as well as increased awareness of workers to wear protective equipment in managing B3 waste. Keyword: B3 waste management, PT. PAL Indonesia (Persero), B3 waste content.